Imagem corporal de crianças pré-púberes no contexto da pandemia da COVID-19 - Vale, Gabriela Fernandes Del (Universidade Federal de São Carlos, 2024)
The COVID-19 pandemic has significantly impacted the quality of life of populations worldwide. Movement restrictions and the need for social distancing limited opportunities for children's leisure and interactions, increasing sedentary behavior and its consequences, such as excess weight. Additionally, family economic instability affected access to healthy and quality food, adequate housing, healthcare, and the supply of basic needs for children. Eating behavior formation begins in childhood. The early years of life are known as a critical phase for establishing food preferences, weight control, and body image formation. Body image refers to the mental and subjective representation we have of our own body. It is how we perceive, think, and feel about our physical appearance and, therefore, how we relate to our body. Given the complex and unique panorama of the COVID-19 pandemic, where media and family influence on children intensified, this study sought to understand the effects of the pandemic situation on the body image of children aged 5 to 7 years 11 months and 29 days and parents' conceptions and attitudes towards nutrition, weight evolution, and health-related quality of life of these children. OBJECTIVE: To analyze, in the context of the COVID-19 pandemic, the body image of children aged 5 to 7 years and 11 months, the prevalence of perception, idealization, and body satisfaction disorders in this population, parents' conceptions and attitudes towards their children's nutrition and weight evolution, and parents' perception of the health-related quality of life of these children. METHOD: Descriptive, cross-sectional, and quantitative research conducted in the Family Health Strategy of the city of São Carlos, state of São Paulo. The research was approved by the UFSCar Research Ethics Committee (CAAE 29370820.7.0000.5504; Opinion: 4.211.811) and conducted with a convenience sample of 239 prepubescent children aged 5 to 7 years and 11 months and their guardians. The children's and guardians' weight, height, and body mass index (BMI) were determined, and the Truby and Paxton Body Image Scale was applied to assess children's perception, idealization, and satisfaction and the guardian's perception of the children. The Stunkard Scale was also applied to assess the guardians' perception, idealization, and satisfaction. The Child Feeding Questionnaire (CFQ) was used to evaluate parental feeding practices and the parent-child relationship regarding nutrition and parental concern about their children's weight evolution. The Pediatric Quality of Life Inventory was used to assess the guardians' perception of the children's quality of life. Results for continuous quantitative variables were presented as mean ± standard deviation. For discrete quantitative variables, mean, median, minimum, and maximum were calculated. Qualitative variables were described as absolute frequency and percentage. Regarding body perception, satisfaction, and idealization analyses, children were divided by sex and BMI classification into eutrophic, overweight, and obesity. For CFQ and quality of life analyses, children were divided by sex and grouped into appropriate weight and overweight. Statistical analyses were performed using JASP® 0.16.3 software. Comparison between means was performed using the Mann-Whitney test or the non-parametric variance test, depending on the number of variables. The association between categorical variables was calculated using the chi-square test. Pearson's correlation test was used to evaluate the degree of correlation between variables with normal distribution, while Spearman's test was applied to others. Odds ratio analysis was performed using logistic regression test, ENTER mode. The analysis of independent variables that could modify a given outcome (odds ratio) was performed using exploratory logistic regression, where independent variables were inserted simultaneously in the initial model (ENTER mode). All logistic regression analysis models had a VIF<5. The internal consistency of the questionnaires was evaluated using Cronbach's alpha test (α). The significance level adopted was 95% (p < 0.05). RESULTS: Female representatives comprised 91.2% of the sample, with 47.3% classified as obese. The children's sample was composed of 45.6% female and 54.4% male, with 10% and 18% classified as obese, respectively. Body perception data revealed inaccuracy in self-perception in 66% of the children, with 69% underestimating and 31% overestimating their BMI. Guardians' inaccuracy regarding children's body perception differed significantly by sex. Overweight boys were considered eutrophic and underweight in 65% of cases. In contrast, overweight girls were considered obese by their parents in 60% of cases. The greater the child's overweight, the greater the body dissatisfaction. Among girls, 82% of the obese, 48% of the overweight, and 34% of the eutrophic were dissatisfied. Among boys, 48% of the obese, 46% of the overweight, and 21% of the eutrophic were also dissatisfied. The influence of the media's aesthetic standards resulted in a desire for smaller bodies and thinner silhouettes in 43% of eutrophic girls and larger bodies in 20% of eutrophic boys. The feeding questionnaire results showed higher scores in the perception of responsibility for the child's feeding and monitoring (p<0.0001) and lower scores in the perception and concern about the child's weight (p<0.0001). There was a positive correlation between children's BMI and perception and concern about the child's weight (p<0.0001). Guardians with lower education levels had lower perception and concern about the child's weight (p=0.034). The quality of life questionnaire results revealed that overweight boys scored higher than girls with appropriate weight in physical capacity (p=0.050). Among overweight boys and girls, the score was higher in the school aspect (p=0.001) and overall aspect (p=0.009). CONCLUSION: The period of social isolation, catalyzed by the pandemic, highlighted the significant influence exerted by family and media on children's body image formation. This context underscores the importance of both verbal and non-verbal messages that shape perceptions around children's bodies. Analyzing guardians' beliefs and attitudes towards nutrition and weight evolution during this global crisis shows an undeniable prioritization of children's nutrition, potentially enhancing adherence to various aspects of nutritional care. Examining sociodemographic determinants, health history, and living standards, it is imperative to recognize the possible interconnection between guardians' emphasis on feeding and monitoring and the complex socioeconomic adversities caused by the pandemic. The difficulty in ensuring minimally adequate nutrition for children may be intrinsically linked to the widespread impoverishment of the population during this period. This dimension must be fully considered when shaping public policies aimed at child health to address nutritional needs effectively. Furthermore, subsequent studies must explore whether there is a disparity in guardians' perception of children's quality of life. It is worth questioning whether overweight children are somehow perceived as more adapted to the pandemic situation, possibly because they present an appearance socially associated with robustness. Understanding these subtler aspects can provide valuable insights to guide future interventions aimed at promoting both physical health and the emotional well-being of children in similar contexts.
"Body image of prepubertal children in the context of the COVID-19 pandemic
Keywords: Imagem corporal; Comportamento alimentar; Qualidade de vida; Crianças; Pais; Body image; Eating behavior; Eating behavior; Children; Parents; CIENCIAS DA SAUDE